Occupational power differentiates employee impacts under continuing change. Issue 4 (13th July 2015) - Rodwell, John; Flower, Rebecca; Demir, Defne
Abstract : Purpose: – The purpose of this paper is to investigate whether occupational social contexts differentiate the processing of changes in the employment relationship, as represented by the psychological contract. Specifically, this study investigates the impact of the psychological contract and justice, with negative affectivity (NA), on medical practitioners or administrative staff in healthcare. Design/methodology/approach: – Samples of 54 medical practitioners (30 percent) and 122 administrative staff (59 percent), primarily providing public services, responded to a cross-sectional survey. Data were analyzed using multiple regression analyses. Findings: – Among medical staff, psychological contract obligations were associated with lower commitment and psychological distress, whereas fulfillment was associated with higher commitment and job satisfaction, yet higher distress. Distributive justice was associated with lower distress, and NA was associated with higher distress. Among administration staff, fulfillment was associated with commitment and job satisfaction, and NA was associated with lower job satisfaction and higher distress. Essentially, reforms are likely to have more impact on less powerful occupations. Practical implications: – Psychological contract fulfillment is a key predictor of hospital employees' commitment and satisfaction, placing clinicians, particularly, under pressure. To retain employees, hospitals must keep their promises. Further, occupational power activates the role of obligations, with practitioners having negative outcomes and holding the organization to account until the obligations are fulfilled. Originality/value: – This study highlights the differential nature of the psychological contract among healthcare employee groups, with differences depending on occupational power.